Physical, Chemical and Preference Levels of Cendol Substituted with Purple Yam Flour (Dioscorea alata L.) - Siti Tamaroh; Chatarina Lilis Suryani; Devi Fitri Astuti Astuti (JITIPARI, 2023)
Purple yam (Dioscorea alata L.) is a local food with many sources of antioxidants, so it becomes a staple food for the community. The addition of purple yam flour to the production of cendol is expected to help increase the selling value of cendol and also purple yam. This research aims to produce cendol with the addition of purple yam flour which has antioxidant activity and liked by the panelists. A completely randomized factorial design was used in this study using 2 factors, namely the treatment of variations in the length of cooking time and variations in the concentration of purple yam flour added, so that 9 treatment combinations were obtained, namely the addition of 10%, 20% and 30% purple yam flour with a cooking time of 10, 15 and 20 minutes. The results showed that there was an effect of cooking time and the addition of purple yam flour concentration had an effect on the chemical properties and preferences of cendol.The best cendol formulation was the addition of 30% purple yam flour and 20 minutes of cooking time. The selected purple yam cendol has nutritional value: ash content 0.082%, antioxidant content 15.55% RSA, phenol content 8.33 mg GAE/g db body and anthocyanin content 15.86 mg/100 g db. Cendol substituted for purple yam flour can ward off free radicals because it has a purple pigment derived from anthocyanin, an antioxidant.